2013
DOI: 10.1063/1.4850975
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on the magnetic properties in Mg doped BiFeO3 with and without oxygen vacancies

Abstract: The magnetic properties of Mg-doped BiFeO3 (BFO) with and without oxygen vacancies are studied through first-principles calculations. The Mg-doping prefers to occupy the ferromagnetic planes and produces an obvious improved magnetization, and the magnetization is linearly enhanced with increasing Mg-doped content, which is consistent with the trend reported in experiment. However, our calculated result is significantly larger than the experimental one, and the reason is revealed that the relative energy differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…. Clearly, the magnetic moments mainly reside on Fe atoms in different magnetic sublattices , and a few of them are located at the C atoms (see Fig. a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…. Clearly, the magnetic moments mainly reside on Fe atoms in different magnetic sublattices , and a few of them are located at the C atoms (see Fig. a).…”
Section: Resultsmentioning
confidence: 99%
“…They found that the enhanced magnetization is ascribed to the partial suppression of modulated spiral spin structure due to structural distortion and the breakdown of the balance between the antiparallel sublattice magnetization of Fe 3+ ions. The magnetic properties of Mg and Al substituted Fe in BFO were investigated by first‐principles calculations . They found that the Mg substitutional doped BFO induced an obvious magnetization and the magnetization was linearly enhanced with the increase of Mg‐doped content.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, multiferroic materials have been perceived as an ideal candidate for novel applications that include but are not limited to spintronics, magnetic field sensors and multiple state memory elements [1]. Researchers are making extensive efforts in fabricating a robust, high performance and relatively less energy expensive memory storage device as a result of huge increasing technological demand over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, multiferroic materials surge in importance for the current technological evolution as it shows significant coupling of ferroelectricity and ferromagnetism specifically at room temperature. Bismuth ferrite (BiFeO 3 -BFO), a class of single-phase multiferroic materials is one of the most promising material for next-generation technological devices owing to its very high both antiferromagnetic Neel temperature of approximately 640 K and ferroelectric Curie temperature of approximately 1100 K [1]. However, ferroelectric polarization measurements of BFO samples show high electrical leakage currents thereby limiting its applications in memory storage devices [2].…”
Section: Introductionmentioning
confidence: 99%
“…8 Other recent experimental examples are the effect of oxygen vacancies on resistive switching in TiO 2Àx lms 9 and on the two-dimensional electron gas at the SrTiO 3 surface. 10 In addition, rst principle and density functional theory investigations have been performed on native point defects in LaAlO 3 , 11 on magnetic properties of Mg doped BiFeO 3 with and without oxygen vacancies, 12 and on energetics of intrinsic defects and their complexes in ZnO. 13 Lany and Zunger calculated the donor level energy of the oxygen vacancy in ZnO to be at or below the midgap, using GW approximation calculations.…”
Section: Introductionmentioning
confidence: 99%